Pelatihan Penggunaan Aplikasi Zoom Untuk Guru Sekolah Dasar Pada Masa Pandemi Covid 19 - Apdoludin Apdoludin; Tri Wiyoko (Universitas Lancang Kuning, 2022)
Distance learning at the elementary school level must continue during the COVID-19 pandemic. The presentation of learning materials must be interesting and interactive so that learning remains effective and efficient. However, the carrying capacity of learning itself has not been properly accommodated. One of them is the ability of teachers to recognize, understand and operate the Zoom cloud meetings application which is still very limited. So that there is a need for training that can improve the ability of these teachers. This training was carried out using a descriptive method consisting of planning, implementation and evaluation stages. Techniques for delivering material with lectures and discussions. There were 21 participants involved in the training. The training activity on the use of zoom cloud meetings at SD Negeri 90/II Talang Pantai in Bungo Dani sub-district has been able to improve teacher understanding and the ability of teachers to use zoom cloud meetings to present online learning.